High-strength PVC (polyvinyl chloride) pipe as well as preparation method and application thereof
By using a composite filler treated with heteropolyacid in PVC tubes, the problem of insufficient compressive performance of existing PVC tubes is solved, and higher compressive performance and longer service life are achieved, while reducing environmental pollution.
Patent Information
- Application Number
- CN202411716112.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-07
AI Technical Summary
The compressive resistance of existing PVC pipes is insufficient, making it difficult to meet the demand for high-strength pipes by modern agricultural irrigation technology.
By treating expanded graphite, methyl benzoate and calcium carbonate with heteropolyacids, a composite filler with a loose porous structure is formed, which is evenly dispersed in the PVC tube, enhancing its compressive resistance.
The compressive resistance of PVC pipes is improved, allowing them to absorb external forces more effectively, extend their service life, and reduce environmental pollution during irrigation.
Smart Images

Figure BDA0005156914060000051 
Figure BDA0005156914060000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of PVC pipe materials, and more specifically, relates to a high-strength PVC pipe and a preparation method and application thereof. Background Art
[0002] With the popularization of automatic irrigation technology in modern agriculture, the market prospect of buried PVC water pipes is broad. Most agricultural irrigation requires the use of PVC water pipes. However, since PVC water pipes need to be buried underground, they have to withstand the damage of various external factors such as concrete, sand, machinery, vehicles, and personnel. Therefore, high-strength buried water pipes with superior compressive performance are currently an important direction for the research and development of new agricultural pipeline systems.
[0003] The popularization and development of modern agricultural technology is rapid. The buried PVC water pipes circulating on the market are difficult to adapt to the pace of development of modern irrigation technology. Various factors such as mechanical damage, human damage, and natural damage will affect the service life of the pipes. Therefore, it is particularly important to improve the compressive performance of buried PVC water pipes.
[0004] Patent CN106398049A discloses a high-toughness graphene-modified PVC material. Graphene is added to the PVC material for modification during its preparation, thereby improving the mechanical properties of the PVC material. However, the aggregation degree of graphene itself is high, and its dispersion in the PVC material is poor, and its compatibility with the PVC material is poor. The improvement of the mechanical properties of the PVC water pipe is limited. Therefore, it is hoped to develop a high-strength PVC pipe with better mechanical properties. Summary of the invention
[0005] In order to solve the defect of poor compression resistance of the prior art PVC pipe, the primary purpose of the present invention is to provide a PVC pipe with excellent compression resistance.
[0006] Another object of the present invention is to provide a method for preparing a PVC pipe.
[0007] Another object of the present invention is to provide an application of a PVC pipe.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] A PVC pipe is prepared from the following raw materials by weight: 100 parts of PVC resin, 13-47 parts of composite filler, and 2-20 parts of other additives; the composite filler is prepared by the following method:
[0010] S1. The expanded graphite, methyl benzoate, heteropoly acid and water were mixed, heated and stirred for reaction, and after completion of the reaction, filtered and dried;
[0011] S2. The reaction product obtained in S1 is heated and stirred and blended with a carbonate to obtain a composite filler;
[0012] The mass ratio of expanded graphite, methyl benzoate, heteropoly acid and carbonate is 1-10:1-5:1-2:10-30.
[0013] The present invention uses heteropolyacid to process expanded graphite and methyl benzoate, so that the interaction between expanded graphite, methyl benzoate and calcium carbonate is obtained to obtain a novel composite filler. It is applied to PVC pipes. Due to the loose porous structure of expanded graphite, it is dispersed in the PVC pipe to form tiny crack gaps. When subjected to external force, the crack gaps can absorb more pressure, thereby enhancing its compressive resistance. Heteropolyacid, due to its higher catalytic activity and redox property, can catalyze the dealkylation reaction of methyl benzoate to obtain benzoic acid groups under the effect of heteropolyacid. Benzoic acid groups are combined with expanded graphite and carbonate surface free hydroxyl groups, so that expanded graphite is fully activated and cross-linked, which is conducive to improving the dispersibility of the composite filler, so that it is evenly dispersed in the PVC pipe, thereby improving the compressive resistance of the PVC pipe. Simultaneously under the effect of heteropolyacid, the surface of expanded graphite is activated, and the porosity of expanded graphite is further increased, which is conducive to enhancing the compressive resistance of the PVC pipe.
[0014] Furthermore, the heating temperature is 60-80°C.
[0015] The invention selects to mix and react expanded graphite, methyl benzoate and heteropoly acid at a temperature of 60-80° C. Under this temperature condition, the dealkylation reaction of methyl benzoate can be promoted, thereby improving the conversion efficiency.
[0016] Furthermore, the reaction time is 2 to 4 hours.
[0017] Furthermore, the pH value of the mixed system in step S1 is 5 to 6. The pH value of the water environment system of the reaction can be controlled by the heteropoly acid, and the composite filler prepared within this pH range is conducive to enhancing the compressive performance of the prepared PVC pipe.
[0018] Furthermore, the drying temperature is 80-90° C., and the drying time is 6-10 hours.
[0019] Furthermore, the carbonate is one or more of calcium carbonate, barium carbonate, and magnesium carbonate. The carbonate is preferably calcium carbonate, and more preferably heavy calcium carbonate.
[0020] Furthermore, the mesh size of the carbonate is 1500 to 2000 meshes.
[0021] The carbonate selected in the present invention is hydrophilic and can absorb a certain amount of bound water molecules on its surface in an air environment. When the temperature rises to 60-80° C., the water molecules are more likely to be deprotonated to form hydroxyl groups on the carbonate surface.
[0022] Furthermore, the stirring and blending is carried out in a high-speed stirrer.
[0023] Furthermore, the other additives are at least one of a calcium zinc stabilizer, a lubricant, titanium dioxide, a processing aid, and an impact modifier.
[0024] Furthermore, the PVC pipe comprises the following raw materials in parts by weight: 100 parts of PVC resin, 13 to 47 parts of composite filler, 1 to 8 parts of calcium zinc stabilizer, 2 to 5 parts of lubricant, 0 to 5 parts of titanium dioxide, 0 to 1 part of processing aid, and 0 to 1 part of impact modifier.
[0025] Furthermore, the lubricant is one or more of paraffin wax, PE wax, and stearic acid. Furthermore, the lubricant is preferably a mixture of polyethylene wax, paraffin wax, and stearic acid, which can reduce the friction between molecules and between molecules and processing equipment during PVC processing, thereby improving the fluidity of the resin and improving the transparency and finish of the product.
[0026] Furthermore, the titanium dioxide is selected from rutile or anatase because of its dense structure, relatively stable, low optical activity, high hiding power and tinting power, which improves the whiteness and weather resistance of PVC.
[0027] Furthermore, the processing aid is an acrylic ester compound, including one or more of LPA40, PA20 or K400P.
[0028] Furthermore, the impact modifier is one or more of acrylates, methyl methacrylate-butadiene-styrene, and chlorinated polyethylene.
[0029] Furthermore, the preparation method of the PVC pipe comprises the following steps: adding the composite filler and each component in the PVC resin and other additives into a hot mixer in proportion for mixing, hot mixing at 140° C. to 145° C., and then extruding and cooling to form.
[0030] The present invention also provides application of the PVC pipe in the field of agricultural irrigation.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention uses heteropoly acid to destroy the ester group of methyl benzoate to open the molecular chain, and at the same time activates expanded graphite, so that the porosity of the expanded graphite is further increased. The expanded graphite interacts with methyl benzoate and calcium carbonate to form a composite filler with a loose porous structure. The components in the composite filler act synergistically so that the composite filler can be evenly dispersed in the PVC pipe. The even distribution of the composite filler and its porous structure enable the PVC pipe to absorb more pressure when subjected to external force, thereby enhancing its compression resistance.
[0033] When the PVC pipe prepared by the present invention is applied to the field of agricultural irrigation, the porous structure of the composite filler contained therein can also adsorb and separate oils and organic macromolecules in the irrigation water, thereby avoiding pollution to the ecological environment. DETAILED DESCRIPTION
[0034] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.
[0035] Examples 1 to 7
[0036] Expanded graphite, methyl benzoate, and heteropolyacid were mixed with water according to the ratio in Table 1 and added to the reactor, the pH value of the solution in the reactor was controlled to be 5, heated to 70°C and stirred for 3 hours, and dried at 85°C for 8 hours after the treatment, and then the obtained product was mixed with heavy calcium carbonate in a high-speed mixer at a temperature of 70°C to obtain a composite filler. Then, according to the ratio of each raw material in Table 1, the filler was mixed with PVC resin and other auxiliary components using a high-speed mixer (hot mixer), hot mixed to 140°C to 145°C, and then discharged into the barrel into the extrusion molding equipment, extruded and cooled to obtain a PVC pipe.
[0037] Example 8
[0038] Expanded graphite, methyl benzoate, and heteropolyacid were mixed with water according to the ratio of Example 1 in Table 1 and added to a reactor, the pH value of the solution in the reactor was controlled to be 4, heated to 70°C and stirred for 3 hours, and dried at 85°C for 8 hours after the treatment, and then the resulting product was mixed with heavy calcium carbonate in a high-speed mixer at 70°C to obtain a composite filler. Subsequently, according to the raw material ratios of Example 1 in Table 1, the filler was mixed with PVC resin and other auxiliary components using a high-speed mixer (hot mixer), hot mixed to 140°C to 145°C, and then discharged into a barrel and entered into an extrusion molding device, and extruded and cooled to obtain a PVC pipe.
[0039] Comparative Example 1
[0040] The difference between Comparative Example 1 and Example 1 is that the raw materials for preparing the composite filler do not contain methyl benzoate, and the specific contents of the remaining raw material components are shown in Table 1.
[0041] Comparative Example 2
[0042] The difference between Comparative Example 2 and Example 1 is that the raw materials for preparing the composite filler do not contain methyl benzoate and expanded graphite, and the specific contents of the remaining raw material components are shown in Table 1.
[0043] Comparative Example 3
[0044] The difference between Comparative Example 3 and Example 1 is that the preparation method of the composite filler is as follows: expandable graphite, methyl benzoate, heteropoly acid and heavy calcium carbonate are mixed with water in the same proportion as in Example 1 in Table 1 and added to a reactor, the pH value of the solution in the reactor is controlled to be 5, heated to 70°C and stirred for 3 hours, and dried at 85°C for 8 hours after the treatment to obtain the composite filler. Subsequently, according to the raw material ratios in Table 1, the filler is mixed with the PVC resin and other auxiliary components using a high-speed mixer (hot mixer), hot mixed to 140°C to 145°C, and then discharged into the barrel into the extrusion molding equipment, and extruded and cooled to obtain a PVC pipe.
[0045] Table 1 Raw material components of PVC pipes of Examples 1 to 7 and Comparative Examples 1 to 2 (in parts by weight)
[0046]
[0047] Performance Testing
[0048] The performance of the PVC pipes obtained in the above examples and comparative examples was characterized, and the specific test items and results are shown in Table 2.
[0049] (1) The test method for the drop weight impact test is the National Standard of the People's Republic of China GB / T 5836.1-2018.
[0050] (2) The test method for tensile yield strength is the National Standard of the People's Republic of China GB / T 5836.1-2018.
[0051] (3) The test method for longitudinal shrinkage is the National Standard of the People’s Republic of China GB / T 5836.1-2018.
[0052] (4) The test method for elongation at break is the National Standard of the People’s Republic of China GB / T 5836.1-2018.
[0053] (5) Ring stiffness (DN / IN=110, wall thickness 3.2 mm) The test method is GB / T 9647-2015 Determination of ring stiffness of thermoplastic plastic pipes.
[0054] (6) Flatness performance test The test method is the flatness test in the National Standard of the People's Republic of China GBT 33608-2017.
[0055] Table 2
[0056]
[0057] From the data of the embodiment in Table 2 above, it can be seen that the PVC pipe prepared by the present invention effectively improves the mechanical properties of the PVC pipe by adding a specific composite filler, and the synergistic effect of methyl benzoate, expanded graphite and calcium carbonate in the composite filler, and its impact performance reaches 40 / 40 without breaking, and the ring stiffness can reach 7.82KN / m 2 The above-mentioned flat performance achieves no cracks or ruptures, has high tensile yield strength and elongation at break, low longitudinal shrinkage, and excellent compressive performance. It can meet the use requirements of buried agricultural water pipes, increase service life, reduce irrigation costs, reduce environmental pollution, and comply with the sustainable development strategy.
[0058] By comparing Example 1 with Example 2, and Example 3 with Example 4, it can be seen that in Example 2 and Example 3, only the content of calcium carbonate is increased, and the content of methyl benzoate is not increased, which will cause the dealkylation reaction of methyl benzoate with expanded graphite and free hydroxyl groups on the carbonate surface to deteriorate, resulting in a decrease in the dispersion performance of the composite filler, thereby reducing the mechanical properties of the PVC pipe.
[0059] In Comparative Example 1, methyl benzoate was not added when preparing the composite filler, resulting in a low degree of activation and cross-linking of the expanded graphite and poor dispersion of the expanded graphite, thereby affecting the mechanical properties of the PVC pipe and resulting in poor compressive performance.
[0060] Comparative Example 2: When preparing the filler, methyl benzoate and expanded graphite were not added, and only heavy carbon calcium was used as the filler. The impact performance was 35 / 40 without breaking, the elongation at break was only 98%, and the ring stiffness was only 5.58 KN / m. 2 , its compressive performance is poor.
[0061] It can be seen from Comparative Examples 1 and 2 that the tensile yield strength, longitudinal shrinkage, elongation at break and flatness performance are improved after the addition of expanded graphite, but the ring stiffness performance is poor. This is because the toughness is enhanced after the addition of expanded graphite, but the lack of methyl benzoate leads to poor dispersion of the composite filler in the PVC pipe, thereby reducing the ring stiffness performance of the PVC pipe.
[0062] It can be seen from Comparative Example 3 that the composite filler obtained by mixing the raw materials of the composite filler at the same time has poor mechanical properties of the PVC pipe made using the composite filler. This is because the corrosion degree of calcium carbonate is large under acidic conditions, which easily causes calcium carbonate to decompose, thus affecting the application of the composite filler in the PVC pipe.
[0063] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A PVC pipe, characterized in that: The composite filler is prepared from the following raw materials by weight: 100 parts of PVC resin, 13-47 parts of composite filler, and 2-20 parts of other additives; the composite filler is prepared by the following method: S1. The expanded graphite, methyl benzoate, heteropoly acid and water were mixed, heated and stirred for reaction, and after completion of the reaction, filtered and dried; S2. The reaction product obtained in S1 is heated and stirred and blended with a carbonate to obtain a composite filler; The mass ratio of expanded graphite, methyl benzoate, heteropoly acid and carbonate is 1-10:1-5:1-2:10-30.
2. The PVC pipe according to claim 1, characterized in that: The heating temperature is 60-80°C.
3. The PVC pipe according to claim 1, characterized in that: The reaction time in step S1 is 2 to 4 hours.
4. The PVC pipe according to claim 1, characterized in that: The pH value of the system after mixing in step S1 is 5-6.
5. The PVC pipe according to claim 1, characterized in that: The carbonate is one or more of calcium carbonate, barium carbonate and magnesium carbonate.
6. The PVC pipe according to claim 1, characterized in that: The other additives are at least one of a calcium zinc stabilizer, a lubricant, titanium dioxide, a processing aid, and an impact modifier.
7. The PVC pipe according to claim 6, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of PVC resin, 13-47 parts of composite filler, 1-8 parts of calcium zinc stabilizer, 2-5 parts of lubricant, 0-5 parts of titanium dioxide, 0-1 part of processing aid and 0-1 part of impact modifier.
8. The PVC pipe according to claim 6, characterized in that: The lubricant is one or more of paraffin wax, PE wax and stearic acid.
9. The method for preparing a PVC pipe according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: placing the composite filler, PVC resin and other components of other additives in a heat mixer according to a certain proportion for mixing, heat mixing at 140-145° C., and then extruding and cooling to form.
10. Use of the PVC pipe according to any one of claims 1 to 8 in the field of agricultural irrigation.
Citation Information
Patent Citations
Highly tenacious PVC material modified by graphite
CN106398049A